2017
DOI: 10.1590/1414-431x20176275
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid-contacting nucleus mediates nociception via release of fractalkine

Abstract: Increasing evidence suggests that the cerebrospinal fluid-contacting nucleus (CSF-contacting nucleus) mediates the transduction and regulation of pain signals. However, the precise molecular mechanisms remain unclear. Studies show that release of fractalkine (FKN) from neurons plays a critical role in nerve injury-related pain. We tested the hypothesis that release of FKN from the CSF-contacting nucleus regulates neuropathic pain, in a chronic constriction injury rat model. The results show that FKN is expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The CSF-contacting nucleus participates in pain modulation (Wang et al, 2014 ; Liu et al, 2017 ; Zhou et al, 2017 ), and it receives several pain-related regions in the subcortex and limbic system. The MS and diagonal band complex is crucial for information processing and chronic pain behavior (Jiang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The CSF-contacting nucleus participates in pain modulation (Wang et al, 2014 ; Liu et al, 2017 ; Zhou et al, 2017 ), and it receives several pain-related regions in the subcortex and limbic system. The MS and diagonal band complex is crucial for information processing and chronic pain behavior (Jiang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The CSF-contacting nucleus is believed to be a unique nucleus in the brain that participates in neuron-neuron and neuron-body fluid crosstalk, and thus possibly influences the regulation of multiple physiological processes [23][24][25][26]. Increasing evidence also suggests that the CSF-contacting nucleus mediates the transduction and regulation of pain signals and might be involved in the modulation of the descending inhibitory system [27][28][29]. However, the precise molecular mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme 6-phosphofructo-2-kinase/fructose-2,6,-bisphophatase 3 (PFKFB3) is commonly overexpressed in cancer where it promotes angiogenesis, migration, and proliferation [ 20 , 21 , 22 ]. More recent studies have shown the involvement of cytoplasmic PFKFB3 in response to DNA-damaging cisplatin in cervical cancer cells [ 23 ] and UV damage in primary mouse embryonic fibroblast [ 24 ].…”
Section: Introductionmentioning
confidence: 99%